Reoperation for Misplaced Pedicle Screws: A Multicenter Retrospective Study. Issue 21 (1st November 2022) - Odate, Seiichi; Fujibayashi, Shunsuke; Otsuki, Bungo; Shikata, Jitsuhiko; Tsubouchi, Naoya; Tsutsumi, Ryosuke; Ota, Masato; Yusuke, Kanba; Kimura, Hiroaki; Onishi, Eijiro; Tanida, Shimei; Ito, Hideo; et al.
Abstract : Study Design: A multicenter retrospective analysis. Objective: This study aims to investigate reoperation of misplaced pedicle screws (MPSs) after posterior spinal fusion (PSF), focusing on neurological complications. Summary of Background Data: The management strategy for MPSs and the clinical results after reoperation are poorly defined. Materials and Methods: Subjects were 10, 754 patients (73, 777 pedicle screws) who underwent PSF at 11 hospitals over 15 years. The total number of reoperations for MPS and patient clinical data were obtained from medical records at each hospital. Results: The rate of reoperation for screw misplacement per screw was 0.17%. A total of 69 patients (mean age, 67.4±16.5 yr) underwent reoperation because of 82 MPS. Reasons for reoperation were neurological symptoms (58 patients), contact with vessels (5), suboptimal bone purchase (4), and misplacement recognized during operation (2). Neurological symptoms were the major reason for reoperation in cervical (5/5 screws, 100%) and lumbo-sacral (60/67 screws, 89.6%) regions. Contact with vessels was the major reason for reoperation in the thoracic spine (6/10 screws, 60.0%). We further evaluated 60 MPSs in the lumbo-sacrum necessitating reoperation because of neurological symptoms. The majority of MPSs necessitating reoperation were placed in the lower lumbar spine (43/60 screws, 71.7%). The mean pedicle breach tended to be larger in the incomplete recovery group than in the complete recovery group (6.8±2.4 vs . 5.9±2.2 mm, P =0.146), and the cutoff value resulting in incomplete resolution was 5.0 mm. Multivariate analysis revealed that medial-caudal breaches ( vs . medial breach, odds ratio: 25.8, 95% confidence interval: 2.58–258, P =0.0057) and sensory and motor disturbances ( vs . sensory only, odds ratio: 8.57, 95% confidence interval: 1.30–56.6, P =0.026) were significant factors for incomplete resolution of neurological symptoms. Conclusions: After reoperation, 70.1% of the patients achieved complete resolution of neurological symptoms. Factors associated with residual neurological symptoms included sensory and motor disturbance, medial-caudal breach, and larger pedicle breach (>5 mm).